DEVELOPMENT OF E-LAPD LEARNING MEDIA TO IMPROVE STUDENTS' METACOGNITIVE SKILLS ON THE MATERIAL ON REACTION RATE FACTORS - Ma’wa , Asya Firosul; Hidayah , Rusly (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine the metacognitive skills of students after using E-LAPD learning media on the material of reaction rate factors. The subjects of this study were students of class XI-2 SMAN 1 Sidayu Gresik. This study used the R&D (Research and Development) research method with the ADDIE model which was limited to the development stage. Data collection in this study used pretest-posttest test instruments and a questionnaire in the form of a metacognitive inventory questionnaire. The results showed that the value of students' metacognitive skills based on metacognitive skills-based tests for the planning indicator was 90.91%; the monitoring indicator was 80.68%; and the evaluation indicator was 86.36%. These results were supported by the acquisition of the metacognitive inventory given at the end of the meeting for the planning indicator of 93.18%; the monitoring indicator was 88.64%; and the evaluation indicator was 89.02%. Overall, students' metacognitive skills increased significantly.